PENDEWASAAN USIA PERKAWINAN SEBAGAI PENCEGAHAN STUNTING PADA SISWA SMA DAN SMK DI DESA CONDRO - Eltasha Meilena Pertiwi; Muchtolifah, Muchtolifah; Fitria Utami, Anisa (Education and Talent Development Center of Indonesia, 2022)
Stunting is a condition of growth and development failure in infants caused by lack of nutritional intake provided. Malnutrition occurs in babies in the womb until the baby is born, but stunting disease will be detected when the baby is 2 years old and above. There are at least 653 stunted babies in East Java. The way to reduce the occurrence of stunted babies is to socialize about the dangers of stunting that occurs due to early marriage. The purpose of holding socialization is to increase adolescents' understanding of the importance of maturing the age of marriage as an effort to reduce the number of stunted babies born. This socialization was carried out at SMA Negeri 1 Pasirian and SMK Negeri Pasirian. This activity received a good response from students of SMA Negeri 1 Pasirian and SMK Negeri Pasirian and there was an increase in knowledge from students as evidenced by discussions held on the sidelines of the event in order to monitor students' understanding of the material that had been delivered. It is hoped that from this socialization activity, students at SMA Negeri 1 Pasirian and SMK Negeri Pasirian can increase students' knowledge and apply the ideal marriage age of 25-year-old men and 21-year-old women.